Gender, Obesity, Fat Distribution and 25-Hydroxyvitamin D - Maria Teresa Guagnano; Damiano D’Ardes; Pamela Di Giovanni; Ilaria Rossi; Andrea Boccatonda; Marco Bucci; Francesco Cipollone (Medicina, 2023)
Background and Objectives: Obesity is a worldwide disease associated with systemic complications. In recent years, there has been growing interest in studying vitamin D but data related to obese subjects are still poor. AIM: The aim of this study was to evaluate the relationship between obesity degree and 25-hydroxyvitamin D [25(OH)D] levels. Materials and Methods: We recruited 147 Caucasian adult obese patients (BMI > 30 Kg/m2; 49 male; median age 53 years), and 20 overweight subjects as control group (median age 57 years), who had been referred to our Obesity Center of Chieti (Italy) between May 2020 and September 2021. Results: The median BMI was 38 (33–42) kg/m2 for obese patients and 27 (26–28) kg/m2 for overweight patients. 25(OH)D concentrations were lower in the obese population compared to the overweight population (19 ng/mL vs. 36 ng/mL; p < 0.001). Considering all obese subjects, a negative correlation was observed between 25(OH)D concentrations and obesity-related parameters (weight, BMI, waist circumference, fat mass, visceral fat, total cholesterol, LDL cholesterol) and glucose metabolism-related parameters. 25(OH)D was also negatively correlated with blood pressure. Conclusions: Our data confirmed the inverse relationship between obesity and blood concentration of 25(OH)D and highlighted how 25(OH)D levels decrease in the presence of glucose and lipid metabolism alterations.